HUBUNGAN KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN PESERTA BPJS KESEHATAN DI WILAYAH KERJA PUSKESMAS SUNGAILIAT TAHUN 2023 - rosnaini ros naini (Masker Medika, 2024)
Introduction: one of the way of developing the healthcare service quality is to give the satisfaction to the patient, which important to do for increasing the function of healthcare service quality to societies by measuring the service quality. Public Health Center (Puskesmas) in Sungailiat has achieving the highest amount. Most of the societies are registered as participants of Healthcare and Social Security Agency (BPJS) which indicates the intensities of visitors of Healthcare and Social Security Agency (BPJS) patients were higher. These variables are related to the service quality such as: tangibles, reliability, responsiveness, empathy, and assurance. The early-results, shows that the the relevant-variables that related to the problem in Sungailiat Public Health Center (Puskesmas) such as: comfortability, human-interaction, and punctuality. Methodology: This research is designed by applying the analytic survey methodology, cross sectional study approach, and Accidental Sampling. There are 110 of Healthcare and Social Security Agency (BPJS) patient samples who taking the treatment in Sungailiat Public Health Center (Puskesmas) area by doing the interview according to the questionnaire. Data are analyzed by using both univariate and bivariate analysis by chi square examination. Results: There were a meaningful-relationship between healthcare service quality in the dimensions of Tangibles, Reliability, Responsiveness, Empathy, and Assurance through Healthcare and Social Security Agency (BPJS) patient satisfaction. Conclusion: Sungailiat Public Health Center (Puskesmas) needs to provide the health brochures and suppliance such as drinking water, also the doctors still need to aware to their punctuality, hospitality, and not to differentiate between Healthcare and Social Security Agency (BPJS) patient and general patience.